Mining vs. Rights: State Responsibility in Protecting Indigenous Communities in Indonesia - Tunggul Wicaksono; Mohamed Feroz Pakkeer Mohideen (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The expansion of nickel mining in Indonesia has accelerated economic growth but intensified environmental harm and rights violations affecting indigenous communities. This study assesses whether the Indonesian state fulfills its obligation to respect, protect, and fulfill indigenous environmental rights in major nickel-producing regions of Sulawesi and Maluku. Using a qualitative case study design, the research combines legal analysis, policy review, and field-based evidence from affected communities. The findings demonstrate three major governance failures: (1) systematic land dispossession without Free, Prior, and Informed Consent (FPIC); (2) regulatory weakening following the 2020 Mining Law and Job Creation Law, which centralized permitting authority and reduced environmental safeguards; and (3) documented environmental degradation linked to public health deterioration, including sharp increases in respiratory illnesses near industrial sites. These patterns reveal a structural implementation gap between Indonesia’s constitutional and international human rights commitments and actual regulatory enforcement. The study contributes empirical evidence on the operationalization of state responsibility in resource extraction contexts and offers a rights-based assessment of mining governance in Indonesia. Strengthening enforcement, accountability, and participatory mechanisms is essential to align mineral development with human rights and sustainable development objectives.